Closing the wounds: One hundred and twenty five years of regenerative biology in the ascidian Ciona intestinalis. Issue 1 (7th July 2014) - Jeffery, William R.; Christiaen, Lionel; Sasakura, Yasunori; Satou, Yutaka; Yasuo, Hitoyoshi
Summary This year marks the 125th anniversary of the beginning of regeneration research in the ascidian Ciona intestinalis. A brief note was published in 1891, reporting the regeneration of the Ciona neural complex and siphons. This launched an active period of Ciona regeneration research culminating in the demonstration of partial body regeneration: the ability of proximal body parts to regenerate distal ones, but not vice versa. In a process resembling regeneration, wounds in the siphon tube were discovered to result in the formation of an ectopic siphon. Ciona regeneration research then lapsed into a period of relative inactivity after the purported demonstration of the inheritance of acquired characters using siphon regeneration as a model. Around the turn of the present century, Ciona regeneration research experienced a new blossoming. The current studies established the morphological and physiological integrity of the regeneration process and its resemblance to ontogeny. They also determined some of the cell types responsible for tissue and organ replacement and their sources in the body. Finally, they showed that regenerative capacity is reduced with age. Many other aspects of regeneration now can be studied at the mechanistic level because of the extensive molecular tools available in Ciona. genesis 53:48–65, 2015. © 2014 Wiley Periodicals, Inc.